Sifat Kepahlawanan Tokoh Bujang dalam Novel "Pulang" Karya Tere Liye - Nita Maya Valiantien; Setya Ariani (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
This study aims to provide an overview of heroic traits shown by the character Bujang in Tere Liye's novel Pulang. The method used in analyzing the data is qualitative method because the data collected and analyzed are in the form of narratives and dialogues in the text related to the heroic traits possessed by Bujang as the main character in the novel. Furthermore, this study uses descriptive techniques to define the heroic traits found in Bujang character. From the results of the analysis, it was found that eight heroic traits possessed by Bujang in the novel Pulang. The traits include caring, charismatic, inspiring, reliable, resilient, selfless, smart, and strong. This finding shows that heroic traits can be found in characters who are involved in the world of crime and also in literary works that use the setting and themes of the criminal world. By having these eight heroic traits, Bujang is a representation of a hero even though he is a character who has a role in the criminal world he lives in the novel.